Assessment of Mortar Shrinkage in Aspect of Organic and Inorganic Modifiers Use. (2015) - Lenart, Małgorzata
Abstract: The shrinkage of cement composites is a very important factor affecting their durability. This is an undesirable property from the technological point of view and hence the subject of many research activities. In the article the results of shrinkage of modified mortars is presented. Lime is a traditionally used additive that has a positive effect on the workability of mortars. In addition, mortar strength and adhesion increases when the lime is added in an amount about 10% c.m. to cement mortar. Among many modern admixtures three of them have been selected for testing. An air entraining and plasticizing admixture dosed at 0.3% c.m. was chosen as typical admixture for mortars (it is also advertised by the manufacturer as "replacing lime" admixture) and two polymer admixtures a styrene-butadiene copolymer and a polyvinyl alcohol both dosed at 5% c.m. The mortars shrinkage was tested in a standard way as well as by the modern system of the so called "gutter". This system allows to record volume changes (shrinkage and expansion) from the beginning when cement composite is put to the gutter. The aim of the research was to determine the effect of mentioned modifiers on cement mortars shrinkage which was tested by two methods: standard and modern.